Hinduism in Milleneal Era, October, 03, 2019 53 APPLICATION OF VEDIC MATHEMATICS ON MULTIPLICATION AND DIVISION PROBLEMS FOR STUDENTS OF PGSD STUDY PROGRAM - I KETUT KERTAYASA (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2019)
Vedic mathematics is uniquely named for formulae to solve problems faster than general solutions. Term of Vedic mathematics based on old Hindu scripture namely Atharvaveda. In this research, sutra (formulae) that applied is the Nikhilam sutra part from 16 sutras on Vedic mathematics. Nikhil sutra is formulae to solve problems about multiplication and division. Research subject on this research is a student of the PGSD Study Program from STAHDS Central Sulawesi. The method that used in this research is Open-Ended who developed by Takahashi, which aims to know how are applying Vedic mathematics, how far the result of student achievement and also what are student responses after got new formulae came from Vedic mathematics. The result of this research is mean of student achievement increase from 68 to 80. On the other hand, data from the questionnaire shows that 90% of the students very agree to apply Vedic mathematics to learning.